2009
DOI: 10.1152/ajpregu.00247.2009
|View full text |Cite
|
Sign up to set email alerts
|

Extreme hypoxemic tolerance and blood oxygen depletion in diving elephant seals

Abstract: Species that maintain aerobic metabolism when the oxygen (O(2)) supply is limited represent ideal models to examine the mechanisms underlying tolerance to hypoxia. The repetitive, long dives of northern elephant seals (Mirounga angustirostris) have remained a physiological enigma as O(2) stores appear inadequate to maintain aerobic metabolism. We evaluated hypoxemic tolerance and blood O(2) depletion by 1) measuring arterial and venous O(2) partial pressure (Po(2)) during dives with a Po(2)/temperature recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(162 citation statements)
references
References 82 publications
5
153
2
Order By: Relevance
“…A P O2 electrode was placed percutaneously in the aorta [8,14] and connected via a waterproof cable to a custom built microprocessor P O2 data logger mounted dorsally midline above the hips. Additionally, a time-depth recorder (TDR) and a radio transmitter were mounted above the logger.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A P O2 electrode was placed percutaneously in the aorta [8,14] and connected via a waterproof cable to a custom built microprocessor P O2 data logger mounted dorsally midline above the hips. Additionally, a time-depth recorder (TDR) and a radio transmitter were mounted above the logger.…”
Section: Methodsmentioning
confidence: 99%
“…Depths of lung collapse in the pressure chamber studies were variable and, at least partially, dependent on inhaled air volume [3,4,7]. In free-diving elephant seals, arterial partial pressure of oxygen ðP O 2 Þ profiles revealed that P O 2 continued to increase in some dives at depths as deep as 83 m, consistent with increased inhaled air volumes and maintenance of gas exchange to greater depths in such dives [8]. Recent modelling suggests that depth of lung collapse in seals and dolphins may be much deeper than estimated in earlier field studies [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The blood PO2 of marine mammals can reach levels below that typically exhibited by 642 terrestrial counterparts (Meir et al 2009). At the same time, the blood of marine 643 mammals can carry more CO2 as carboxyhemoglobin than terrestrial mammals (Tift 644 et al 2014), and they may be more tolerant of higher PCO2 levels and better able to 645 buffer its effects (Castellini 1991; Lenfant et al 1970).…”
Section: Physiological Constraints To Diving 565mentioning
confidence: 99%
“…The 742nd amino acid is the same (Thr) in the sperm whale, beluga whale, and elephant seal, but it is Ala in the Yangtze finless porpoise and mole rat. The elephant seal, the most well-demonstrated diving marine animal, routinely tolerates extreme hypoxemia during dives to completely utilize the blood O 2 store and maximize aerobic dive duration (Meir et al 2009). The full-length cDNA sequences of three HIF-α isoforms were identified and characterized from northern elephant seal muscle (Soñanez-Organis et al 2013).…”
Section: Discussionmentioning
confidence: 99%